A harmonized trust assisted energy efficient data aggregation scheme for distributed sensor networks. (August 2019) - Latha, A.; Prasanna, S.; Hemalatha, S.; Sivakumar, B.
Abstract: Security and energy optimization in Wireless Sensor Network (WSN) have a direct impact over device and network performance. The bridging gap between optimization and security needs to be curtailed so as to achieve secure optimization in this resource constraint networks. This manuscript presents as three-fold integrated scheme that governs secure neighbour selection, energy efficient routing and seamless aggregation that serve a multi objective purpose for WSN. We propose a Trust Assisted- Energy Efficient Aggregation (TA-EEA) scheme that improves overall aggregation precision with limited constraints in neighbour reliability and aggregation. The threefold process of TA-EEA ensures trusted neighbour selection, duty cycle based energy conservation and responsive congestion control for seamless transmission. These processes intend to minimize the energy utilization of the nodes to prolong the lifetime of the network with lesser control overhead. The trade-off between energy and security is exploited to progress efficient energy consumption under controlled overhead with higher packet delivery ratio.